Flexor tend on injury of hand at zone II Early or delayed suture ? - Al bayatti, Mohammed A. Fadil; Alkafagi, Medhat A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: The healing of a sutured tendon in the hand usually occur with an unwanted amount of scarring that defeat good results. Many variables has been studied over many decades; timing of repair M’as a matter of debate. Zone II is the area where those variables mostly affect the results of treatment. Objective: To study and evaluate the results of early or delayed repair under the effects of our local variables. Method: Prospective study of 85 patients, which had flexor tendon repair at zone II by primary repair, delayed primary repair and tendon graft. Results: Results showed a primary repair ended with better functional results than those with delayed repair and than those with tendon graft. Excellent & good results were 83.7% in the early repaired group versus 43.8% in the delaved groups; these results were statically significant; I’ 11.1)1)1)2. Conclusion: We conclude that early suture is better than delayed suture and call on casualty doctors to refer patients to hand surgery unites to have better end results in this difficidt area of treatment.